2002
DOI: 10.1021/jf0115847
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Oxidative Degradation of White Wines and How They Are Affected by Selected Technological Parameters

Abstract: The negative effects of oxygen on white wine quality and the various factors which influence it (including temperature, dissolved oxygen, pH, and free SO(2)) are well documented both at the sensory and compositional levels. What is less defined is the quantitative relationship between these parameters and the kinetics of the development of the negative effects of oxidation. The experiment presented here attempts to generate data which can be used to predictively model the oxidative degradation of white wines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 8 publications
(4 reference statements)
5
109
0
3
Order By: Relevance
“…The addition of SO2 to these samples lowered the perception of the oxidised/aged character slightly. SO 2 binds acetaldehyde, lowering its perception in wine, but it seems that the oxidised aroma of wine is not correlated with the acetaldehyde concentration (Silva Ferreira et al, 2002). The barnyard/medicinal character also increased in the 3 mg O2/L/month treatment between four and six months of treatment.…”
Section: Figure 11mentioning
confidence: 90%
“…The addition of SO2 to these samples lowered the perception of the oxidised/aged character slightly. SO 2 binds acetaldehyde, lowering its perception in wine, but it seems that the oxidised aroma of wine is not correlated with the acetaldehyde concentration (Silva Ferreira et al, 2002). The barnyard/medicinal character also increased in the 3 mg O2/L/month treatment between four and six months of treatment.…”
Section: Figure 11mentioning
confidence: 90%
“…A number of trace aroma compounds have been identified as major contributors to these aroma attributes, including various aldehydes, lactones and acetals (Escudero et al, 2000a;2000b;Silva Ferreira et al, 2002b;2003b). The aldehydes are especially important because of their possible impact on wine aromatic composition (Escudero et al, 2000b;Silva Ferreira et al, 2003b;Culleré et al, 2007).…”
Section: Monoterpenesmentioning
confidence: 99%
“…Aroma attributes that develop due to the formation of new oxidation compounds have been described as honeylike, farmfeed, hay, woody-like, toasted, dry fruits, caramel, overripe fruit, apple, oxidised apple, acetaldehyde, cooked, aldehyde and liquor (Toukis, 1974;Noble et al, 1987;Renouil, 1988;Halliday & Johnson, 1992;Chrisholm et al, 1995;Escudero et al, 2002;Silva Ferreira et al, 2002b). These types of unpleasant descriptors are unwanted in wines, and winemakers go to great lengths to avoid the formation of the chemical compounds responsible for these attributes.…”
Section: Introductionmentioning
confidence: 99%
“…methylglyoxal). This pathway was shown to be the main source of methional in white wines treated with oxygen (Silva Ferreira et al, 2002). Silva Ferreira et al (2003) in a further study did not find that methional was present in a Port wine treated with oxygen, and suggested that the decrease in MTP would lead to the formation of other compounds as yet unidentified.…”
Section: Thioether Alcoholsmentioning
confidence: 92%